Asias industrial transformation the role of manufacturing and global value chains Part 1. - Jesus,Felipe (Metro Manila, Philippines Asian Development Bank, 2018)
The single most important factor that explains East Asias development success was its fast structural transformation toward industrialization, manufacturing in particular.
Keywords: Industrialization; Industrial revolution -- Sources; Industrialization -- East Asia; Electronic books